ANALISIS PENGENDALIAN INTERN ATAS PIUTANG PADA PT. BPR RAJEKWESI SUMBERREJO BOJONEGORO - Novi Vizainiyah (J-MACC, 2020)
Internal control is a framework that consists of components that are interrelated in conducting its activities in order to control the running of the company and to secure the company's assets, to make regulations on the policy to be followed by management. The analysis used in this research is to use the concept of internal control COSO models. The purpose of this study was to determine whether the application of internal control of accounts receivable at PT. BPR Rajekwesi Sumberrejo been effective. The location of the research at Jl. Raya Sumberrejo No. 105, Sumberrejo, Bojonegoro. PT. BPR Rajekwesi Sumberrejo a regional-owned enterprises engaged in receiving deposits in the form of loans, deposits, savings, and / or other forms. So it has a very large amount of accounts receivable. This study uses a quantitative descriptive test the internal control receivable refers to the COSO framework on the components of internal control. The results of this study showed that overall internal control of receivables is effective, can be seen in the total calculation that shows the value of 903 (located between the interval 815-1007), where management has been applying the concepts and principles of internal control.